Cluster randomised trial of the effects of timing and duration of early childhood interventions in Odisha - India: Study protocol - Orazio P. Attanasio; Britta Augsburg; Jere R. Behrman; Sally Grantham-McGregor; Pamela Jervis; Costas Meghir; Angus Phimister; Marta Rubio-Codina (Institute for Fiscal Studies (IFS), 2019)
Many children in developing countries grow up in unstimulating environments, leading to deficiencies in early years' developmental outcomes, particularly cognition and language. Interventions to improve parenting in the first 3 years of life have a clear impact on these outcomes, but the sustainability of effects is mixed, particularly for scalable interventions. There is little evidence of the effect of following-up an early life intervention with another one immediately afterwards. The objective of this study is to help fill this gap.
Keywords: 330